Developing a simulation program for classic and updated Hodgkin and Huxley's voltage clamp experiments - Reyes-Lazalde, A.; Reyes-Monreal, M.; Pérez-Bonilla, M. E. (Revista Mexicana de Ingenieria Biomedica, 2016)
Hodgkin and Huxley´s works were the starting point for generating mathematical models for explaining, reproduce the experimental results and predict the behavior of voltage-sensitive ion channels in the axon. The high costs of these experiments avoid its implementation in teaching degree. An educational alternative is virtual experiments using computer simulations. In this work, the development of a simulator that reproduces step by step the classic experiments of Hodgkin and Huxley on the conductance of voltage-dependent channels in squid giant axon is presented. The simulator was developed in Visual Basic language, ver 5.0 for Windows environment. It consists of four modules: (1) ionic currents simulation; (2) classical Hodgkin and Huxley´s experiments; (3) current version model; (4) action potentials. It comprises connecting interface screens that allow simulate and compute the values of the variables associated with the channel conductance.The user can perform an unlimited number of virtual experiments that will facilitate the understanding of the subject.